The binary vs. privative status of verbal inflectional morphology: The case of Germanic. - Castillo-Orihuela, Concepción (My University, 2023)
This paper argues that the binary opposition [+/-past] entails that Tpast contrasts with Tpres in computing a more complex kind of t- or tense-feature in the morpho-syntax and in exhibiting one more Vocabulary Item or marker in the morpho-phonology. It is argued that this situation used to be the case for all Germanic languages generally speaking, but that it is no longer the case for Present Day English or Mainland Scandinavian.
Keywords: Lenguas germánicas - Morfosintaxis; Flexión (Gramática); Lenguas germánicas - Conjugación; Germanic; Inflection; Morpho-syntax